Studi Literatur: Efektivitas Penggunaan Media Quizizz Terhadap Pembelajaran IPA di Berbagai Tingkat Pendidikan di Indonesia - Abroto Abroto; Na'imah Na'imah (The Prime is under the provision of the Study Program of Islamic Elementary School Teacher Training (PGMI) of Sekolah Tinggi Ilmu Tarbiyah Aqidah Usymuni Sumenep Indonesia, 2025)
Science learning is often considered a subject that requires a complex understanding of concepts, which can leave students feeling bored. The main problem behind the need for the use of quizizz in science learning: lack of student involvement and motivation in science learning, many students feel less interested in science subjects because they are considered difficult or boring. Science learning often focuses on complex theories and concepts. This research is a qualitative research with a literature review approach, which aims to examine in depth the use of interactive learning media of the Quizizz Game. Data was collected through literature studies by browsing scientific articles, journals, seminar proceedings, and books and research reports from various sources such as Google Scholar, and SINTA. The researcher set inclusion criteria, namely articles that discuss the use of Quizizz in science learning, published between 2023 and 2025, and has gone through a peer-review process. From the qualitative data analyzed, it was found that Quizizz media is very effective in increasing learning motivation, learning outcomes, activeness, and even as a technology-based evaluation tool at various levels of education. However, its success is greatly influenced by careful planning, appropriate question design, and digital infrastructure readiness. Most studies state that the use of Quizizz is able to increase students' motivation to learn in science subjects. The interactive game format, the existence of a score and ranking system, and attractive visuals are the main factors that encourage students to be more enthusiastic in participating in learning.